Fieldnotes : the Makings of Anthropology - Sanjek, Roger; Sanjek, Roger (Cornell University Press, 2019)
Thirteen distinguished anthropologists describe how they create and use the unique forms of writing they produce in the field. They also discuss the fieldnotes of seminal figures-Frank Cushing, Franz Boas, W.H.R. Rivers, Bronislaw Malinowski, and Margaret Mead-and analyze field writings in relation to other types of texts, especially ethnographies. Unique in conception, this volume contributes importantly to current debates on writing, texts, and reflexivity in anthropology.